Creative Teaching Thrives in Public School Classrooms - Vilches, Maria Luz C (Archīum Ateneo, 2010)
In the heightened competition that characterizes globalization, knowing one's culture and keeping in touch with its most intimate values and aspirations can give the individual plenty of needed comfort. Without a sense of inner security that our culture, values, and aspirations provide, it is easy to succumb in the heat of battle. - From the Introduction by Fernando N. Zialcita.